2016
DOI: 10.1371/journal.pgen.1005963
|View full text |Cite
|
Sign up to set email alerts
|

De Novo and Rare Variants at Multiple Loci Support the Oligogenic Origins of Atrioventricular Septal Heart Defects

Abstract: Congenital heart disease (CHD) has a complex genetic etiology, and recent studies suggest that high penetrance de novo mutations may account for only a small fraction of disease. In a multi-institutional cohort surveyed by exome sequencing, combining analysis of 987 individuals (discovery cohort of 59 affected trios and 59 control trios, and a replication cohort of 100 affected singletons and 533 unaffected singletons) we observe variation at novel and known loci related to a specific cardiac malformation the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 79 publications
(97 reference statements)
3
63
0
1
Order By: Relevance
“…Diabetes mellitus is associated with a multitude of metabolic disturbances, and elevated glucose levels appear to be the primary teratogen for diabetic embryopathy (12). Consistent with this, improved glucose control during pregnancy is associated with reduction in CHD risk and, alternatively, poor glycemic control is linked to a higher risk for CHD in offspring (10).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Diabetes mellitus is associated with a multitude of metabolic disturbances, and elevated glucose levels appear to be the primary teratogen for diabetic embryopathy (12). Consistent with this, improved glucose control during pregnancy is associated with reduction in CHD risk and, alternatively, poor glycemic control is linked to a higher risk for CHD in offspring (10).…”
Section: Discussionmentioning
confidence: 84%
“…Studies of genetic contributors have identified an increasing number of genes associated with CHD (7)(8)(9). The importance of gene dosage for the occurrence of cardiac malformations has been shown, along with the concept of an oligogenic etiology for CHD, supporting the concept that mild alterations in gene expression levels may lead disease phenotypes (10)(11)(12)(13). Similarly, numerous environmental risk factors for CHD have been reported, each of which increases the risk of having a child with CHD (14).…”
Section: Introductionmentioning
confidence: 94%
“…Notably, de novo mutations accounted for at least 20% of CHD with associated extracardiac and neurodevelopmental abnormalities 75 . While these mutations are more prominently associated with syndromic rather than non-syndromic CHD 80 , there is a small but measurable contribution to isolated CHD (CHD not associated with a known syndrome, and without any extracardiac malformations or neurodevelopmental abnormalities) 81 , which may become more clearly delineated when larger cohorts are analyzed 8275 .…”
Section: Beyond Large Structural Variation and Mendelian Chd: The Impmentioning
confidence: 99%
“…CHD is caused by many factors, including intrauterine infection, environmental pollution, and inheritable factors [2]. It was reported that the primary cause of mortality from birth defects was related to the structure or function of the heart lesion [3].…”
Section: Introductionmentioning
confidence: 99%